2006
DOI: 10.1080/00016340500324241
|View full text |Cite
|
Sign up to set email alerts
|

Prepregnancy risk factors for placental abruption

Abstract: Although univariate analysis identified many risk factors, only smoking, uterine malformation, previous cesarean section, and history of placental abruption remained significant after multivariate analysis, increasing the risk of placental abruption in subsequent pregnancy. It may be possible to approximate the risk for placental abruption based on these simple prepregnancy risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
77
2
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 29 publications
12
77
2
4
Order By: Relevance
“…Correlation of placental abruption with both chronic hypertension and preeclampsia has been clearly established (8,(16)(17)(18)(19). Similarly, in our study an association of both chronic hypertension and preeclampsia with abruption was seen, consistent with the literature (p<0.05).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Correlation of placental abruption with both chronic hypertension and preeclampsia has been clearly established (8,(16)(17)(18)(19). Similarly, in our study an association of both chronic hypertension and preeclampsia with abruption was seen, consistent with the literature (p<0.05).…”
Section: Discussionsupporting
confidence: 82%
“…Especially hypertensive diseases of gestation, additional morbidities, previous history of C/S and advanced maternal age increased the risk of abruption and there was a significant correlation between prematurity and placental abruption. The rate of a history of placental ablation varies between 0.3% and 1% in the literature (10)(11)(12). In our study, this rate was 0.66%.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…A incidência do DPP é variada nos diversos serviços, observando-se de quatro a 35 casos a cada 1.000 gestações, discordância que pode ser justificada pelas diferentes características das populações analisadas 1,11,15,16 . Além disso, estudos têm demonstrado, nos últimos anos, aumento da incidência de DPP 17,18 , que pode estar relacionado às mudanças nos fatores de risco a que estão expostas as gestantes na atualidade e ao incremento tecnológico na propedêutica obstétrica que tem contribuído para o diagnóstico acurado do DPP.…”
Section: Discussionunclassified
“…24,25,[34][35][36][37][38] Previous studies have reported that both maternal cigarette smoking and alcohol consumption during pregnancy are associated with abruptio placentae. 4,5,27,28,39 We could not correlate these variables in our study since there were no smokers and alcoholics in our study.…”
Section: Comparison With Previous Studiesmentioning
confidence: 92%